Yukon passage - Stewart, James; Lipscomb, James (WQED/Pittsburg : National Geographic Society, 1977)
A documentary about four young men who retrace the passage of oldtime prospectors who flocked to the gold-rich Klondike in 1897-98
Keywords: Klondike gold fields; Yukon territory -- Description and travel